Diversity of culturable microfungi of coal mine spoil tips in Svalbard - Iliushin, Vadim A.; Kirtsideli, Irina Y.; Vlasov, Dmitry Y. (Polar Science, 2022)
The fungal complexes of the coal mine spoil tips around the settlement Barentsburg (Svalbard) were studied. Samples were taken from coal mine spoil tips with different ages (formed, 10-years, 30-years and 50-years). Arctic tundra soils were used as the control. The indicators of change were the species composition, diversity level, dominant groups of species and isolate density of fungal communities. The harsh arctic conditions and the inhospitality of the rock substrate determined the relatively low diversity of microfungi. Only 15 species of microfungi were identified in the samples from formed spoil tip, while in the samples from 50-year-old tip the number of microfungi species increased to 29. The average density of microfungi (CFU/g) for all sampling depths of the coal mine spoil tips was low. But this indicator increased with the age of spoil tips. The density of microfungi isolates also increased with depth in the coal mine spoil tips. The composition of the dominant species of microfungi changed with the age of the spoil tips increased. The convergence of the microfungal complexes of spoil tips and control arctic soils indicates gradual increase stability of mycobiota in disturbed areas. journal article